KAZAKHSTAN’S ECONOMY IN THE GRIPS OF THE WORLD FINANCIAL CRISIS - BABAK, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2009)
During the past two years, the world economy has been functioning in the conditions of a global financial crisis that is having an impact on the economic development of almost every country in the world. The republic of Kazakhstan, which succeeded during the years of its independence to occupy a dignified place in the world economy, is no exception. It was the first CIS country (and one of the first in the world) to become caught in the grips of the financial crisis. It should be emphasized that the current crisis has primarily affected highly developed countries. Beginning in the U.S., it quickly pulled Germany, France, Japan, Great Britain, and other countries into its orbit. Although in terms of its main economic indices, Kazakhstan lags far behind these countries, there were many reasons why it followed right behind the U.S. and fell victim to the crisis earlier than many others. The first signs of the crisis phenomena appeared in this country as early as the end of the summer of 2007. It stands to reason that all the aspects of the global financial and economic crisis will become a target of comprehensive scientific study, from which the necessary practical conclusions will have to be drawn. Today it is too early to talk about the possible results of these studies, but some reasons for what is going on are already obvious. The main one seems to be that the theoretical concepts prevalent in world economic science over the past decades have proven untenable. In the second half of the 20th century, particularly after the collapse of the world socialist system, most countries took a so-called neo-liberal approach to economic development problems. This approach espouses the principle of liberalism (free market relations in the economy) and the concept of monetarism (amplification of the role of financial capital in economic development). In compliance with this, free market relations are viewed as the only possible regulator of the development of national economies and the world economy as a whole, while the state is allotted the role of passive observer. But when national banks and corporations found themselves on the brink of bankruptcy, it was the governments of the largest capitalist countries that had to fork out huge amounts of money from the treasury to help them avoid collapse of their financial and economic systems. So the theory of liberal monetarism as a universal mechanism of economic regulation has not justified itself. At the beginning of April 2009, a meeting of the leaders of the twenty largest nations of the world was held in London to look for ways out of the crisis. Several decisions were adopted that essentially meant a rejection of the neo-liberal theory. However, President of Kazakhstan Nursultan Nazarbaev had been questioning its validity even earlier. At the beginning of March 2009, he realized that it was wrong for the republic’s economy to be oriented solely toward market relations and said that the economy should be “hand-steered,” which undoubtedly implied intensifying the government’s role in the country’s economic life.